Evaluation of the Creativity of Physical Education Teachers in Sports and Health at Private Elementary Schools in Pedurungan District (Journal of Physical Education and Sports, 2022)
Quality and quality education is determined by educators (teachers). The research objectives are (1) to evaluate the originality factor of the creativity of PE teachers; (2) to evaluate the creativity elaboration factor of PE teachers; (3) to evaluate the creativity flexibility factor of Private Elementary School PE teachers in Pedurungan District, Semarang City. This research is maxed method research using a quantitative descriptive approach. This study's data sources were Principals, PE teachers, and elementary students in the Pedurungan sub-district, Semarang City. The data analysis used is descriptive analysis, classified into two groups of data: quantitative data in the form of numbers and qualitative data in words or symbols. The results of this study (1) Originality factor, the results of reliability calculations from item statement items. Which has been tested r < 0.67 Weak interpretation. (2) the elaboration factor of the PE teacher's creativity, the elaboration factor of 9 items that have been tested, r < 0.67 Weak interpretation. This is because PE teachers only learn by relying on the material in printed books. The lack of variation in the movements and the learning feels monotonous (3) flexibility factor The creativity of the PE teacher flexibility factor is 11 items tested with r < 0.67 unique interpretation.. Based on the study's results, it was concluded that the flexibility factor had been implemented well in the three creative factors of PE teachers in the Pedurungan sub-district. Applying the originality and elaboration factor of PE teachers in the Pedurungan sub-district is still weak.